SKRINING AKTIVITAS ANTIOKSIDAN JAMU SUBUR KANDUNGAN KOMERSIAL - Ahmad, Mujahidin (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Selection of traditional medicine is often considered as a choice since the affordable price and low side effects than chemical drugs. One of the well-known herbal medicine produced and consumed in java is Madura Herbal Medicine (MHM). MHM